The effect of NaOH on the kinetics of Hydrogen production from sodium borohydride using Ni-based catalysts doped with Ruthenium - Fernandes, Vitor (2012)
Previous work by the authors has demonstrated a high rate and high yield hydrolysis of sodium borohydride in the presence of a Ni-Ru catalyst synthesized by wet chemistry. The catalyst has been fully characterized and utilized more than 300 times, exhibiting high stability and durability. In this work, the effect of temperature on the reaction rate was studied and the activation energy of the process estimated for temperatures up to 65 ºC. Typical data in the form of an Arrhenius type relationship showed two slope regions suggesting a change of mechanism that lead to a more accentuated role of ruthenium for temperatures higher than 45 ºC. This effect is maintained with increasing Ru doping of the catalyst. The effect of NaOH as a stabilizer was also studied and the role of Ni and Ru in the hydrolysis of sodium borohydride is under study on the basis of data obtained for various Ru concentrations and data for 100% Ni and 100% Ru as catalysts. An increase in the concentration of Ruthenium in the catalyst allowed effective utilization of the catalyst without the need for the stabilizer, minimizing the induction reaction time. Excellent catalytic activity and catalyst minimal deactivation for sodium borohydride hydrolysis are characteristic of the series of Ni-Ru catalyst synthesized by wet chemistry used in this work.